Faktor-Faktor Yang Mempengaruhi Ibu Melakukan Imunisasi Lengkap Pada Anak Usia 12 Bulan Di Wilayah Puskesmas Permata Sukarame Kota Bandar Lampung - Setiawati Setiawati; Riska Wandini; Mutiara Veny Yulia (Malahayati Nursing Journal, 2022)
ABSTRACT: THE INFLUENCING FACTORS OF COMPLETE IMMUNIZATION PRACTICE CONDUCTED BY WOMEN FOR 12 MONTH BABIES AT PERMATA HEALTH CENTER OF SUKARAME OF BANDAR LAMPUNG  Introduction: Based on a pre-survey conducted on six centers for pre and post-natal health cares at the working area of Permata Health Center of Sukarame, there were 153 out of 346 children receiving complete immunization in their 13, 18, 24 months. The 153 children from six types of natal health care were 36 babies from Mekar Sari II, 59 babies from Aster Kuning, 7 babies from Bahtera, 16 babies BetikHati, 14 babies from Kasih Ibu, and 20 babies from Permata Sukarame. Objective: This study was to identify the influencing factors of complete immunization practice conducted by women for 12-month babies at Permata Health Center of Sukarame of Bandar Lampung in 2019. Method: The study was quantitative. The research design was an analytical survey with a cross-sectional approach. The samples and population of this study consisted of 88 people. The sampling technique was purposive sampling. The statistical analysis was chi-square. Result: The frequency category was presented as 109 women (76,8%) having good knowledge, 76 women (53,5%) having a supportive attitude,83 women (58.5%) having low education level background, 50 women (56.8%) living in supporting surroundings, and 55 babies (38.7%) got complete immunization. The relation varied from knowledge with p-value 0.003 (α0.05), attitude with p-value 0.001 (α0.05), education level with p-value 0.001 (α0.05), and the environment with p-value 0.001 (α0.05). Conclusion: The result indicated that there were correlations among knowledge, attitude, education level, and environment towards immunization practice for babies. The health practitioners are suggested to provide comprehensible knowledge for the women for vaccine understanding in giving immunization.  Keywords: knowledge, attitude, education level, immunization practice  INTISARI: FAKTOR-FAKTOR YANG MEMPENGARUHI IBU MELAKUKAN IMUNISASI LENGKAP PADA ANAK USIA 12 BULAN DI WILAYAH PUSKESMAS PERMATA SUKARAME KOTA BANDAR LAMPUNG  Pendahuluan: Berdasarkan hasil prasurvey di 12 posyandu Wilayah Puskesmas Permata Sukarame, terdapat 142dari 222 anak yang telah mendapat imunisasi lengkap pada usia 12  bulan, pada posyandu Mekar Sari II  sebanyak 24 anak, Aster Kuning 20  anak, Bahtera 14 anak, betik Hati 16 anak, Kasih ibu 18 anak, Permata Sukarame 19 anak, Teratai 16 anak, Sakura II 21 anak, Sakura I 20 anak, Manggis 16 anak, Matahari 17 anak, Nusa indah 21 anak.Tujuan: Untuk mengetahui faktor-faktor yang mempengaruh ibu melakukan imunisasi lengkap pada anak usia 12 bulan di Wilayah Puskesma Permata Hati Sukarame Kota Bandar Lampung Tahun 2019.Metode: Jenis penelitian ini adalah Kuantitatif. Desain penelitian ini Survei Analitik dengan pendekatan cross sectional.Populasi dan sampel yang akan diambil adalah sebanyak 142 orang, pengambilan sampel pada penelitian adalah purposive sampling Uji statistik menggunakan uji chi  squareHasil : Kategori frekuensi terbanyak berdasarkan dan pengetahuan kurang baik sebanyak  109 orang (76,8%), sikapmendukung sebanyak 76 orang (53,5%), pendidikan rendah 83 orang (58,5%), imunisas lengkap sebanyak 81 orang (57,0%), hasil uji chi square p-value 0,003 p-value 0.001, p-value 0.001Kesimpulan :Yang artinya terdapat antara hubungan pengetahuan, sikap, pendidikan, dengan pelaksanan imunisasi pada anak. Dapat memberikan atau pengetahuan yang benar kepada masyarakat tentang vaksi sehingga meningkatkan motivasi dalam melakukan imunisasi. Kata Kunci     : Pengetahuan, Sikap, Pendidikan, Pelaksanaan Imunisasi